PREPARING YOUNG PEOPLE FOR FAMILY LIFE PSYCHOLOGICAL FUNDAMENTALS (ResearchJet Journal of Analysis and Inventions, 2021)
This article deals with the preparation of students for family life and taking into account our nationality, national values, family values, social environment in the formation of students' understanding of the psychological and ethnic characteristics of the problem, family skills and family life.